A Forgotten Issue: Distributional Effects of Day Care Subsidies in Germany - Michaela Kreyenfeld; Christa Katharina Spieß; Gert G. Wagner (Institute for the Study of Labor (IZA), 2000)
In general child care subsidies are widely accepted as a means to create equal chances for mothers in the labour market as well as for children. Although there is a general consensus that the use of child care should be publicly supported, there is no consensus on how this should be done. Moreover, there is little knowledge on the distributional effects of child care subsidies. In order to assess whether public expenditures are targeted efficiently, it is, however, vital to know which social groups profit most from the public expenditures on children?s day care and if taxpayers money is spent effectively. In Germany, as in other European countries, child care subsidies are mainly provided ?in-kind?. Local communities and NPOs provide child care slots for children, which are – except for a small fee - free of charge. In this study we estimate the distributional effects of state funded child day care in Germany using microdata of households and data on the expenditure of public funded child care. Major results are that child care subsidies only carry modest redistributional effects. In the first place, it is the middle income range that profits from the public provision of children?s day care. This contradicts common public policy recommendations, which state that low income families should be the first target of child care subsidies.
Keywords: H2; H4; D1; D3; 330; Child day care; child care subsidies; distributional effects; social policy; Einkommensverteilung; Kinderbetreuung; Subvention; Deutschland